How to Be A Gardener Book Two. Secrets of Success - Titchmarsh A. Alan (Accompanies the Television series)
How to Be a Gardener: Book Two is the follow-up to the phenomenally successful How to Be a Gardener: Book One by Alan Titchmarsh, aka TV's Mr Gardening. Titchmarsh's title suggests what many will agree with, namely that gardening is more a state of being than an activity, something to which more or less every waking hour and thought must be dedicated. (The less ambitious Delia Smith, it might be noted, did not call her trilogy How to Be a Cook). Nonetheless, like the first volume, this is resolutely, and rightly, aimed at the virtual beginner--perhaps the ideal reader is the owner of a garden whose sole effort to date has been to look guiltily out of the window from time to time and swear to get round to doing something about it. This volume, subtitled Secrets of Success, adds to the basic techniques of the first in the practical context of making and maintaining gardens. They aren't secrets, of course--or they won't be once this book starts selling--but the wisdom and knowledge of an experienced gardener and teacher. A quick whisk (three pages) through garden history since the Middle Ages and we're off into an introductory consideration of garden types and how to make the best of what nature and the previous owner have bequeathed. Structure and style established, the remainder of the book the practice. The rather mysteriously titled Vertical Gardening turns out to be about fences, hedges, pergolas--anything that goes up rather than along. Patios, beds and borders, water features, vegetables and wildlife and covered (i.e., greenhouse and conservatory) gardens are each explored in depth, giving all the information the nervous gardener will need to bring it all together. This book privileges good advice and endless reassurance over high concepts. There really is no excuse now not to get on with it. --Robin Davidson